Skull Base Inverted Papilloma: A Comprehensive Review. (31st December 2012) - Wassef, Shafik N.; Batra, Pete S.; Barnett, Samuel
Abstract : Skull base inverted papilloma (IP) is an unusual entity for many neurosurgeons. IP is renowned for its high rate of recurrence, its ability to cause local destruction, and its association with malignancy. This paper is a comprehensive review of the reports, studies, and reviews published in the current biomedical literature from 1947 to September 2010 and synthesize this information to focus on its potential invasion to the base of the skull and possible intradural extension. The objective is to familiarize the clinician with the different aspects of this unusual disease. The role of modern diagnostic tools in medical imaging in order to assess clearly the limits of the tumors and to enhance the efficiency and the safety in the choice of a surgical approach is pointed out. The treatment guidelines for IP have undergone a complex evolution that continues today. Radical excision of the tumour is technically difficult and often incomplete. Successful management of IP requires resection of the affected mucosa which could be achieved with open surgery, endoscopic, or combined approach. Radio and chemotherapy were used for certain indications. More optimally research would be a multicenter randomized trials with large size cohorts.